Duration of watching TV and child language development in young children - Silva Audya Perdana; Bernie Endyarni Medise; Erni Hernawati Purwaningsih (Paediatrica Indonesiana, 2017)
Background Many factors contribute to language development in children. About 5-8% of children in Indonesia experience delayed language skills. Young children need appropriate stimulation for optimal development. Children who watch television (TV) for long periods of time may receive less two-way interaction, the appropriate stimulation for learning. As such, shorter duration of the appropriate stimulation may impede language development in small children.Objective To assess for an association between duration of watching TV and language development in young children.Methods This cross-sectional study was done with primary data collected from questionnaires. Subjects, aged 18 months to 3 years, were from a Jakarta-area community health center (Puskesmas) Jatinegara and the Pediatric Growth and Development Clinic, Cipto Mangunkusumo Hospital, Jakarta. Their language development was tested using the Developmental Pre-screening Questionnaire (Kuesioner Pra Skrining Perkembangan, KPSP) and the Early Language Milestone (ELM Scale 2) test.Results From a total of 84 subjects, 47 (56%) had normal and 37 (44%) had delayed language development. Duration of watching TV was categorized as <4 hours per day or >4 hours per day. Children who watched TV >4 hours/day (OR 4.4; 95%CI 1.68 to 11.7; P=0.002), and children who watched both Indonesian and English language TV programs (OR 14.7; 95%CI 1.77 to 123.0; P=0.004) had higher risk of language delay. Other variables such as sex, first age exposed to TV, use of gadgets, and TV in the bedroom had no significant associations with delayed language development.Conclusion Children who watch TV >4 hours/day had four times higher risk of developing language delay. In addition, those who watch TV programs in both Indonesian and English, also have a 14.7 higher risk of delayed language development.